Transradial percutaneous coronary intervention in high-risk patients. (July 2015) - Khoo, Chee W; Holroyd, Eric W; Butler, Rob; Nolan, James; Mamas, Mamas A
Percutaneous coronary intervention (PCI) is the commonest form of revascularization in patients with coronary heart disease. The benefit of early invasive treatment with PCI in patients presenting with acute coronary syndromes are well accepted. Traditionally, PCI has been performed via the femoral access with significant risks for the development of access site-related bleeding complications. Increased international adoption of the transradial access site for PCI procedures has been shown to reduce such major access site-related bleeding complications and mortality, especially in the high-risk patient groups. We provide a brief overview of the historical perspective on transradial approach and the evidence supporting its use. We then discuss the current data supporting transradial access in high-risk populations and factors that have limited its adoption.